Noise in the World. - Bogen, Jim (Philosophy of Science, 2010)
This essay uses Györgi Buzsáiki's use of EEG data to draw conclusions about brain function as an example to show that investigators sometimes draw conclusions from noisy data by analyzing the noise rather than by extracting a signal from it. The example makes vivid some important differences between McAIlister's, Woodward's, and my ideas about how data are interpreted.